'Doing great things for the world': merit and the justice politics of young people receiving an elite educational scholarship. Issue 6 (2nd November 2021) - Charles, Claire; Black, Rosalyn; Keddie, Amanda
ABSTRACT: Higher Education policy researchers have highlighted the link between merit and privileged social background with respect to who is most likely to win merit-based scholarships in Universities. Yet little is known about how students from various social backgrounds may inhabit such a scholarship. In this paper, we draw on theorisations of the relationship between meritocracy and justice in order to analyse the subjective work of several undergraduate students who are positioned as winners in a meritocracy, due to being recipients of a generous merit-based scholarship. We explore the different techniques these students use to justify their access to privilege, unpacking their notions of justice, and consider them in relation to their social backgrounds. We argue that recognising their distinct constructions of merit and justice can help advance understanding of how the logics of meritocracy are (re)made in the context of University merit scholarships.